Factors Influencing Public-Sphere Pro-Environmental Behavior among Mongolian College Students: A Test of Value–Belief–Norm Theory - Liu, Xianwei; Zou, Yang; Wu, Jianping (Sustainability, 2018)
Value–belief–norm (VBN) theory provides a valuable framework for identifying the social-psychological determinants of various types of pro-environmental behavior. However, limited empirical study has tested the applicability of VBN theory in the western minority areas of China. Given Mongolian college students’ crucial role in promoting the sustainable development of the Inner Mongolia Autonomous Region (IMAR) of China, this study investigates how VBN clusters of variables, namely, values, the new environmental paradigm (NEP) and pro-environmental personal norms (PPN), influence Mongolian college students’ self-reported public-sphere pro-environmental behavior (PSPB). The subjects were 1034 Mongolian college students from three large public universities in Hohhot. A structural equation model (SEM) and bootstrapping analyses revealed that: (1) altruistic values have a significant positive influence on PSPB, egoistic values negatively influence PSPB, and biospheric values have no significant influence on PSPB; (2) egoistic values negatively predict NEP and biospheric values positively predict NEP, whereas altruistic values have no direct impact on NEP; (3) NEP has a positive influence on PPN; (4) PPN has a significant positive impact on PSPB; and (5) biospheric and egoistic values have an indirect effect on PSPB through NEP and PPN. The findings provided evidence for the cross-cultural applicability of VBN theory in a Mongolian college student sample. Theoretical and practical implications were discussed, and recommended directions for future research were suggested.